Identification of early-stage silicosis through health screening of stone benchtop industry workers in Victoria, Australia. (28th October 2020) - Hoy, Ryan F; Glass, Deborah C; Dimitriadis, Christina; Hansen, Jessy; Hore-Lacy, Fiona; Sim, Malcolm R
Abstract : Objectives: The popularity of high silica content artificial stone has been associated with emergence of severe, progressive silicosis as a major health issue affecting workers in the stone benchtop industry. This population-based health assessment programme has been implemented with the aim of identifcation of silica-associated disease at a preclinical stage. Methods: All current and former workers from the stone benchtop industry in the State of Victoria are offered free health assessments. Primary evaluations include a standardised questionnaire, physical examination, spirometry and gas transfer assessment and International Labour Organisation-categorised chest X-ray. Secondary evaluations include high-resolution CT chest, blood tests and a respiratory physician evaluation. Results: At the end of the first 12 months, 86/239 (36%) workers who had completed secondary evaluation were diagnosed with silicosis (65 simple silicosis and 21 complicated silicosis). 22 had worked in the industry for less than 10 years at the time of diagnosis. Of those with simple silicosis, 80% of workers reported breathlessness only with strenuous exercise (modified Medical Research Council score of 0), and lung function was well preserved (prebronchodilator forced vital capacity mean 99.8% predicted (SD 13.6), diffusion capacity of the lung for carbon monoxide mean 96.2% predicted (SD 18.0)). Antinuclear antibodies were detected in 37% with silicosis and 24% without silicosis. Conclusion: Early results from this comprehensive health assessment programme have indicated a high proportion of referred artificial stone benchtop workers have silicosis, including many with early-stage disease. The common finding of antinuclear antibodies suggest significant potential for autoimmune disease in this occupational group.